Quantum Mechanics - Merzbacher, Eugen (New York : John Wiley & Sons Inc, 1999)
Rapid advances in quantum optics, atomic physics, particle physics and other areas have been driven by fantastic progress in instrumentation (especially lasers) and computing technology as well as by the ever-increasing emphasis on symmetry and information concepts-requiring that all physicists receive a thorough grounding in quantum mechanics. This book provides a carefully structured and complete exposition of quantum mechanics and illustrates the common threads linking many different phenomena and subfields of physics.
Keywords: Quantum Mechanics; Scattering